Fatigue life prediction of orthotropic steel deck strengthened with UHPC under stochastic traffic load - Deng, Ming; Yi, Ju (Frontiers in Materials, 2023)
In recent years, the ultra-high performance concrete (UHPC) has been increasingly used to strengthen orthotropic steel decks (OSD) to solve the cracking problems at fatigue-prone details and pavement damage. In this paper, the fatigue life of a cable-stayed orthotropic steel decks bridge under stochastic traffic loads is calculated before and after the orthotropic steel decks strengthened with the ultra-high performance concrete layer. The traffic data of the real bridge for 1 week is first obtained based on the weigh-in-motion system. Then, a stochastic traffic load on the bridge is simulated for its service life by the Monte Carlo method. A fatigue life analysis framework, which includes the traffic load simulation, a refined finite element model, the S-N curve and Miner linear cumulative damage criterion, is proposed for fatigue life prediction of orthotropic steel decks. For the bridge before reinforcement, the predicting results for the fatigue life of three fatigue-prone details, including the scallop cutout, rib-to-diagram and rib-to-deck joint are basically consistent with that of the actual bridge inspection results. After strengthening by ultra-high performance concrete, the fatigue life of the three structural details are increased from 15.87, 13.89, and 32.26 years to more than 100 years, respectively, as compared with the original orthotropic steel decks structure.